EQUIVALENCE ISSUES IN TRANSLATION - Dossova, S N; Kambarov, B К; Shoinzhanova, М Т (Journal of Oriental Studies, 2016)
This article deals with key issues of translation equivalence and different approaches of Kazakh, Russian and foreign scientists to define it.